The impact of MK‐467 on plasma drug concentrations, sedation and cardiopulmonary changes in sheep treated with intramuscular medetomidine and atipamezole for reversal. Issue 3 (19th January 2018) - Adam, M.; Raekallio, M. R.; Keskitalo, T.; Honkavaara, J. M.; Scheinin, M.; Kajula, M.; Mölsä, S.; Vainio, O. M.
Abstract : The effect of MK‐467, a peripheral α2 ‐adrenoceptor antagonist, on plasma drug concentrations, sedation and cardiopulmonary changes induced by intramuscular (IM) medetomidine was investigated in eight sheep. Additionally, the interactions with atipamezole (ATI) used for reversal were also evaluated. Each animal was treated four times in a randomized prospective crossover design with 2‐week washout periods. Medetomidine (MED) 30 μg/kg alone or combined in the same syringe with MK‐467 300 μg/kg (MMK) was injected intramuscular, followed by ATI 150 μg/kg (MED + ATI and MMK + ATI) or saline intramuscular 30 min later. Plasma was analysed for drug concentrations, and sedation was subjectively assessed with a visual analogue scale. Systemic haemodynamics and blood gases were measured before treatments and at intervals thereafter. With MK‐467, medetomidine plasma concentrations were threefold higher prior to ATI, which was associated with more profound sedation and shorter onset. No significant differences were observed in early cardiopulmonary changes between treatments. Atipamezole reversed the medetomidine‐related cardiopulmonary changes after both treatments. Sedation scores decreased more rapidly when MK‐467 was included. In this study, MK‐467 appeared to have a pronounced effect on the plasma concentration and central effects of medetomidine, with minor cardiopulmonary improvement.